Fate of Fumonisin B2 (FB2) during Vinification and Wine Storage: Fining Agents for the Removal of FB2 in Wine - D. Perera; P. D. Prenzler; S. Savocchia; C. C. Steel (Australian Journal of Grape and Wine Research)
Background and Aims. Fumonisins are a group of mycotoxins produced by some isolates of black aspergilli. This study examines the dynamics of fumonisins during winemaking and storage and the role of fining agents in the removal of FB2, the most prevalent fumonisin produced by black aspergilli. Methods and Results. Chardonnay grapes were inoculated with a fumonisin-producing strain of Aspergillus welwitschiae and fumonisins were quantified at different stages of vinification. The stability of fumonisins was studied at 13 and 25°C using Chardonnay wine spiked with FB2. Activated charcoal, calcium bentonite, yeast hulls, and a nonallergenic polysaccharide of nonanimal origin (NO (OX)) were evaluated as fining agents for FB2 removal from wine. Fumonisins were quantified by LC-MS/MS. During vinification most of the fumonisins were removed with the solids, with only 3% of the fumonisins found in the grapes being transferred to the wine. Fumonisin FB2 was stable in white wine for at least 4 months, but was reduced by 42% after 8 months at 25°C. Activated charcoal and bentonite were able to remove more than 80% of FB2 in white wine. Conclusions. Vinification can lead to the partial removal of fumonisins. The use of fining agents and wine storage leads to further reduction. Significance of the Study. This study demonstrates the fate of fumonisins during vinification and wine storage and the potential use of fining agents for amelioration of fumonisin contamination.